Mezhdunarodnye sportivnye organizatsii i sportivnaya politika na sovremennom etape - Vasin, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
Review on some aspects of the actual sport political situation, e.g. concerning sports in TV, popularity of sports in different countries etc.